Preferences on treatment decision making in sarcoma patients: prevalence and associated factors$dresults from the PROSa study - Salm, Hanna; Schuler, Markus K.; Hentschel, Leopold; Richter, Stephan; Hohenberger, Peter; Kasper, Bernd; Andreou, Dimosthenis; Pink, Daniel; Mütze, Luise; Arndt, Karin; Hofbauer, Christine; Schaser, Klaus-Dieter; et al. (Oncology research and treatment, 2025)
Introduction: The impact of being diagnosed with a life-threatening illness may influence preferences to participate in treatment decisions. The objective of this analysis was to identify factors that are associated with sarcoma patients wanting to take a more active or passive role. Methods: Data were obtained as part of a nationwide multicenter study (PROSa) aiming to investigate the structure and quality of medical care of sarcoma patients in Germany and their determinants. The study was conducted between 2017 and 2020 in 39 study centers. For the present analysis, cross-sectional data of adult patients with sarcoma of any entity were analyzed. Control preference was measured with the control preference scale (CPS). Preferences were divided in patient-led, shared, or physician-led-decision-making. Associated factors were analyzed exploratively using multivariable multinominal logistic regression models. We included socio-economical and medical variables with stepwise backward variable selection. Results: We included 1,081 patients (48.6% female). 402 patients (37.2%) preferred to be in control about treatment decisions, while 400 patients (37.0%) favored shared responsibility. 25.8% (n = 279) wished to rather leave the control to the treating physician. Older patients were more likely to prefer shared decision-making than younger patients aged 18-40 years (age group: >75 years: odds ratio [OR] 0.53, 95% confidence interval [95% CI] 0.28; 0.99). Patients with a metastatic tumor desired shared decision making compared to those without metastases (metastasis: OR 1.61, 95% CI 1.09; 2.38). When comparing the patients who preferred physician-led decision making with those who favored to be in control, older patients also preferred leaving the control to the physician and were less inclined to make the decisions by themselves: (18 to >40 years vs. >75 years: OR 0.28, 95% CI 0.15; 0.55). With secondary school (8/9 years) as reference, patients holding a high school degree were more likely to prefer patient-led decision-making over physician-led decision making (OR 2.00, 95% CI 1.26; 3.09). Patients with sarcoma of the abdomen/retroperitoneum were more predisposed to taking control in treatment decisions compared to those with sarcoma of the back/spine or lower limb (back/spine: OR 0.18, 95% CI 0.06; 0.54, lower limb: OR 0.56, 95% CI 0.37; 0.85). With an income of EUR 1,250/month as reference, patients with a higher income were more likely to take control (>EUR 2,750/month: OR 1.7, 95% CI 1.0; 3.1). Conclusion: The findings of our study demonstrate that patients with metastatic disease are more likely to seek a joint decision, while those of higher age and lower education level are less likely to actively participate in treatment decisions. The results suggest that the impact of advanced illness may influence preferences to participate. Practice Implication: These results can provide the basis for clinicians to tailor decision-making approaches according to patient characteristics, such as age, education, and disease status. Recognizing that older and less educated patients may prefer physician-led decisions while younger, more educated patients often seek active involvement; clinicians can better align their communication strategies. Providers should promote shared decision-making for patients with metastatic disease, supporting personalized engagement. By adopting a flexible, patient-centered approach, healthcare providers can enhance patient satisfaction and improve the quality of care for sarcoma patients.